Prevalence of burnout and its risk and protective factors among healthcare workers in the Middle East, North Africa, and Turkey: a systematic review and meta-analysis - Alhassan, Mohammed A.; Alarabi, Mohammed A.; Alhassan, Shaden Abdulrahman; Albalawi, Waled M.; AlRabiah, Ebraheem S. (Frontiers in Psychology, 2025)
BackgroundBurnout, defined as persistent work-related stress, is a critical concern among healthcare workers (HCWs), particularly in high-demand environments such as the Middle East, North Africa, and Turkey (MENAT) region. This systematic review and meta-analysis aimed to assess the pooled prevalence of burnout and examine its associated risk and protective factors among HCWs in the MENAT context.MethodsA comprehensive search of studies published between 2013 and 2024 identified 123 studies involving 36,769 participants. Only studies using the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) were included. Burnout was evaluated across its three dimensions: emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA). The protocol is registered with PROSPERO (CRD420251051167).ResultsThe pooled prevalence was 40% for high emotional exhaustion, 31% for high depersonalization, and 38% for low personal accomplishment. The overall mean scores were 22.02 for EE, 10.07 for DP, and 25.49 for PA. Substantial heterogeneity across studies reflected wide variation in healthcare system capacity and workforce conditions. Burnout was more pronounced in countries such as Saudi Arabia, Iran, and Turkey. Common risk factors included high workload, lack of institutional support, younger age, and female gender. Protective factors were linked to increased autonomy, leadership support, and strong peer relationships.ConclusionBurnout is prevalent among HCWs across the MENAT region, with significant variability across countries. Targeted interventions to reduce occupational stressors and enhance protective workplace structures are urgently needed to safeguard provider wellbeing and improve healthcare delivery.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251051167, identifier CRD420251051167